Implementation of rapid manufacturing for mass customisation. Issue 1 (6th February 2017) - Deradjat, Dominik; Minshall, Tim
Abstract : Purpose: The purpose of this paper is to increase the understanding of how companies can implement rapid manufacturing (RM) (i.e. the use of additive manufacturing (AM) technologies for final part production) for mass customisation (MC), drawing upon the experiences of firms in the dental sector (one of the major users of AM technologies). Design/methodology/approach: A framework for implementation of RM for MC was developed from the literature to guide the data gathering. Data from six case companies in the dental sector implementing RM for MC, supplemented with insights from their respective AM machine providers and software companies, were used to analyse how companies implement RM for MC and what considerations and challenges they face in the process. Findings: The study shows how implementation of RM for MC entails different considerations depending on the stage of implementation and maturity of involved technologies. In total, 26 challenges have been identified that seem to play a crucial role in implementation. The paper suggests that RM can enable MC in manufacturing by achieving both a high number of units produced and as well as a high level of customisation of each product. Originality/value: Based on the review of the literature, no case studies exist that investigate companies implementing RM for MC despite literature having suggested RM as an enabler for MC in manufacturing for many years.